2006
DOI: 10.1001/archotol.132.6.650
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Central Compartment Elective Lymph Node Excision in the Staging and Treatment of Papillary Thyroid Cancer

Abstract: To determine the incidence of nodal involvement and assess the role of elective lymph node (LN) exploration and/or dissection in staging of tumors and treatment of patients with papillary thyroid cancer.Design: Retrospective medical chart review.Setting: Academic tertiary care medical center.Patients: One hundred patients diagnosed with papillary thyroid cancer by fine-needle aspiration or intraoperative frozen section who underwent total thyroidectomy with central compartment cervical LN exploration.Main Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
102
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 21 publications
13
102
1
4
Order By: Relevance
“…In a similar type of comparison study, Hughes et al [6] found no difference in TG, but they noted an upstaging of almost one third of their cN0 patients older than 45 to Stage III disease based on pathologically positive central nodes (pN1a), which subsequently affected the dose of postoperative radioactive iodine (150 mCi for pN1 vs. 30 mCi for pN0). Similar upstaging of patients had previously been noted by Shindo et al [7]. Studies have yet to clarify whether this upstaging translates into identification of truly higher risk patients who may benefit from more aggressive RAI dosing, or whether these upstaged patients are overtreated.…”
supporting
confidence: 67%
“…In a similar type of comparison study, Hughes et al [6] found no difference in TG, but they noted an upstaging of almost one third of their cN0 patients older than 45 to Stage III disease based on pathologically positive central nodes (pN1a), which subsequently affected the dose of postoperative radioactive iodine (150 mCi for pN1 vs. 30 mCi for pN0). Similar upstaging of patients had previously been noted by Shindo et al [7]. Studies have yet to clarify whether this upstaging translates into identification of truly higher risk patients who may benefit from more aggressive RAI dosing, or whether these upstaged patients are overtreated.…”
supporting
confidence: 67%
“…Extrathyroidal invasion (16), multifocality (17) and bilateral thyroid tumors of PTMC (18) are the important risk factors in lymph node metastasis that represent biological characteristics of progress. Although the study by McCarthy et al (19) reported that multifocality is highly homologous within the gland and is not associated with tumor invasion, Shindo et al (17) and Chow et al (20) found that neck lymph node metastasis and tumor multifocality remain significantly correlated, which is the major reason for lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Preferimos avaliar presença de linfonodos no compartimento central e lateral pela ultrassonografia pré-operatória. Observamos no intraoperatório toda região e cadeias júgulo-carotídeas, realizamos exame de congelação em eventuais linfonodos encontrados e, se confirmada metástase, preferimos o esvaziamento de todo compartimento central e não apenas "Picking procedure", afinal tal procedimento é incompleto e está associado a maior freqüência de recorrência (26,27). A reabordagem do compartimento central, já manipulado, devido à recorrência, certamente eleva o percentual do hipoparatireodismo e principalmente o de lesão do nervo recorrente (28 foi comprovado que linfadenopatia metastática com rotura capsular apresenta pior prognóstico (29).…”
Section: Discussionunclassified